Safety, Efficacy and Quality of Life Analysis of Dolutegravir versus Efavirenz Antiretroviral Therapy in HIV Patients at the ART Centre, Madhesh Institute of Health Sciences, Janakpur, Madhesh Province, Nepal - Mahaseth, Rameshwar; Yadav, Binod Kumar; Telee, Lal Babu Sah; Chaudhary, Ramdev; Sah, Vijay Kumar (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: In several countries, the Dolutegravir (DTG)-based regimen is generally preferred as first-line antiretroviral therapy (ART) over the Efavirenz (EFV)-based regimen for people living with HIV (PLHIV). This study aimed to evaluate the safety and tolerance of DTG- versus EFV-based regimen for human immunodeficiency virus (HIV) treatment in ART Center, Provincial hospital, Janakpur, Nepal. We sought to determine Efficacy, the rate of adverse events (AEs) and quality of life (QOL) among patients treated at Provincial Hospital, but the evidence in developing countries is limited. Materials and methods: This analysis is divided into two groups’ namely DTG and EFV-based regimen groups. There are altogether 40 patients in each regimen before and after the use of Dolutegravir (DTG) regimen for one year in ART Center, MIHS, Janakpur. Blood routine checkup were done for anemic, renal function, liver functions, and QOL assessments in each regimen groups. Results: The median age was 31 years, 58% were male. Participants were on ART for 48 weeks on EFV- before using DTG based- regimen. The results revealed that 87.28% of total age groups in DTG based regimen had good quality of life (QOL) in 2021 than that of 65.46% in EFV based regimen in 2020. Almost 90.9 % of Migrants among high-risk groups in DTG-based regimen had good quality of life (QOL) in 2021 than that of 50% of EFV -based regimen in 2020. Conclusions: DTG-based regimen was effective, well tolerated with improved quality of life (QOL) and less adverse effects (AEs).